Design and thermodynamic assessment of a biomass gasification plant integrated with Brayton cycle and solid oxide steam electrolyzer for compressed hydrogen production. (9th December 2020) - Yilmaz, Fatih; Ozturk, Murat; Selbas, Resat
Abstract: In this paper, a comprehensive thermodynamic evaluation of an integrated plant with biomass is investigated, according to thermodynamic laws. The modeled multi-generation plant works with biogas produced from demolition wood biomass. The plant mainly consists of a biomass gasifier cycle, clean water production system, hydrogen production, hydrogen compression, gas turbine sub-plant, and Rankine cycle. The useful outputs of this plant are hydrogen, electricity, heating and clean water. The hydrogen generation is obtained from high-temperature steam electrolyzer sub-plant. Moreover, the membrane distillation unit is used for freshwater production, and also, the hydrogen compression unit with two compressors is used for compressed hydrogen storage. On the other hand, energy and exergy analyses, as well as irreversibilities, are examined according to various factors for examining the efficiency of the examined integrated plant and sub-plants. The results demonstrate that the total energy and exergy efficiencies of the designed plant are determined as 52.84% and 46.59%. Furthermore, the whole irreversibility rate of the designed cycle is to be 37, 743 kW, and the highest irreversibility rate is determined in the biomass gasification unit with 12, 685 kW. Highlights: A biomass gasification based multigeneration plant is proposed for useful products. A comprehensive thermodynamic analysis is modeled with EES software. Hydrogen generation and compression sub-systems are suggested and investigated. The energy and exergy efficiencies of the examined plant are 52.84% and 46.59%, respectively. The total hydrogen generation rate is found as 0.074 kg/s.